Seed encrusting with salicylic acid: A novel approach to improve establishment of grass species in ecological restoration. - Simone Pedrini; Jason C Stevens; Kingsley W Dixon (PLoS ONE)
To achieve global ambitions in large scale ecological restoration, there is a need for approaches that improve the efficiency of seed-based interventions, particularly in overcoming the bottleneck in the transition from germination to seedling establishment. In this study, we tested a novel seed-based application of the plant stress modulator compound salicylic acid as a means to reduce seedling losses in the seed-to-seedling phase. Seed coating technology (encrusting) was developed as a precursor for optimising field sowing for three grass species commonly used in restoration programs, Austrostipa scabra, Microlaena stipoides, and Rytidosperma geniculatum. Salicylic acid (SA, 0.1mM) was delivered to seeds via imbibition and seed encrusting. The effects of SA on seed germination were examined under controlled water-limited conditions (drought resilience) in laboratory setting and on seed germination, seedling emergence, seedling growth and plant survival in field conditions. Salicylic acid did not impact germination under water stress in controlled laboratory conditions and did not affect seedling emergence in the field. However, seedling survival and growth were improved in plants grown from SA treated seeds (imbibed and encrusted) under field conditions. When SA delivery methods of imbibing and coating were compared, there was no significant difference in survival and growth, showing that seed coating has potential to deliver SA. Effect of intraspecific competition as a result of seedling density was also considered. Seedling survival over the dry summer season was more than double at low seedling density (40 plants/m2) compared to high seedling density (380 plants/m2). Overall, adjustment of seeding rate according to expected emergence combined with the use of salicylic acid via coating could improve seed use efficiency in seed-based restoration.